Contemporary Photography Works of Ruang MES 56: Idea, Interpretation of Information, and Model of Creation - Irwandi Irwandi (IJCAS (International Journal of Creative and Arts Studies), 2019)
Ruang MES 56 is a contemporary photography-based Art Institute in Yogyakarta. This independent art institution has been widely known through its various worksin international arts events. The resulting works are not merely personal, butappear to be conceptually charged and based on preproduction information. Thisarticle will discuss the discovery of ideas, excavations, and interpretations ofinformation made by artists of Ruang MES 56 in the creation of works. Morespecifically, this research will dig deeper into what kinds of information artistsare searching for in the creation, and how they influence the appearance of thework they produce. The research data will be obtained through interviews andstudies of documents owned by selected artists of Ruang MES 56 members. Theexpected result of this research is the discovery of the created patterns of creation, and can reveal the process of transforming the information that has been collected into the form artworks.